National Society of Genetic Counselors Code of Ethics: Explication of 2017 Revisions. Issue 1 (27th October 2017) - Senter, Leigha; Bennett, Robin L.; Madeo, Anne C.; Noblin, Sarah; Ormond, Kelly E.; Schneider, Kami Wolfe; Swan, Kelli; Virani, Alice; ,
Abstract: The Code of Ethics (COE) of the National Society of Genetic Counselors (NSGC) was adopted in 1992 and was later revised and adopted in 2006. In 2016, the NSGC Code of Ethics Review Task Force (COERTF) was convened to review the COE. The COERTF reviewed ethical codes written by other professional organizations and suggested changes that would better reflect the current and evolving nature of the genetic counseling profession. The COERTF received input from the society's legal counsel, Board of Directors, and members‐at‐large. A revised COE was proposed to the membership and approved and adopted in April 2017. The revisions and rationale for each are presented.